Functional Constipation during Pregnancy - Salma Zaman, Saeeda Bano, Khadija Noor, Khaula Noor, Jamshid Feroze, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To establish whether or not functional constipation is commonplace among pregnant women in our cultural setting. Methodology: A cross-sectional study was conducted in the Department of Obstetrics and Gynaecology, Sahiwal Medical College, Sahiwal, from June 2022 to December 2022. Three hundred and forty pregnant women were identified using the reliable Rome III criteria and enrolled. Constipation-related knowledge and demographic information, including the treatment method used, were identified through a questionnaire. SPSS version 21 was used for the statistical analysis. Results: According to Rome Criteria III, 220(64.7%) pregnant women had functional constipation. Furthermore, the study described a statistically significant correlation (0.010) between the type of measure used to resolve constipation and experiencing functional constipation during pregnancy, with 26% of pregnant women using ispaghol. There is a statistically significant (p = 0.0001) correlation between functional constipation and awareness. Of the pregnant women in the present study who reported having functional constipation, 43% reported having good awareness about constipation and its consequences in pregnancy, while 30% reported being unaware of the fact (P = 0.010). Conclusion: Functional constipation during pregnancy is prevalent. Additionally, majority of the women had a good understanding of the dangers of constipation during pregnancy. Keywords: Pregnancy, Awareness, Constipation, Remedies